The Endomorphism Semigroup of a Special Semigroup (Journal of Bangladesh Academy of Sciences, 2009)
The endomorphism semigroup for a class of commutative semigroups, called special semigroups, will be studied their structures will be determined in some important cases. AMS Classification : 20 Keywords: Special semigroups, freeness, divisibility, direct sums, endomorphism, endomorphism semigroup. doi: 10.3329/jbas.v32i1.2442 Journal of Bangladesh Academy of Sciences, Vol. 32, No. 1, 55-60, 2008